Contextual risk factors in the use of electric kick scooters: An episode sampling inquiry. (July 2021) - Lee, Kyung-Jun; Yun, Chan Hyeok; Yun, Myung Hwan
Abstract: Among various personal mobility devices, the electric kick scooter is the most actively distributed product worldwide in the form of personal use or sharing services. With the dissemination, numerous accidents related to electric kick scooters occurred. In order to verify the factors that increase the risk of using electric kick scooters, we designed a questionnaire structure and analysis methodology that can sufficiently collect the context-of-use of the electric kick scooters. A total of 21 electric kick scooter users were recruited in South Korea and risk episodes were collected from their daily life experiences for three weeks. The two-step clustering methodology performed to classify the collected risk episodes and the decision tree performed to interpret classified risk episodes to define four risk episode groups. Based on the classified episode group, the distribution of contextual factors was reported. After assigning "Average perceived danger level" and "Frequency" values to each factor, k-means clustering was performed to extract the high-risk factors affecting the safety of the electric kick scooters. From crosstabulation of extracted high-risk factors, key risk issues of some product elements, such as wheels, brake, and suspension, are reported and risk scenarios that users could experience described. These results are expected to enhance safety by contributing to the design stage of electric kick scooters. The analysis methodology can be used to reflect the context-of-use of any target product to extract design issues and key scenarios.